SINGLE-CRYSTAL ELASTIC PROPERTIES OF ALUNITE, KAL3 (SO4)2(OH)6 - Majzlan J.; Speziale S.; Duffy T.S.; Burns P.C. (My University, 2006)
The single-crystal elastic constants of natural alunite (ideally KAl3(SO4)2(OH)6) were determined by Brillouin spectroscopy. Chemical analysis by electron microprobe gave a formula KAl3(SO4)2 (OH)6. Single crystal X-ray diffraction refinement with R1 = 0.0299 for the unique observed reflections (Fο > 4σF) and wR 2 = 0.0698 for all data gave a = 6.9741(3) Å, c = 17.190(2) Å, fractional positions and thermal factors for all atoms. The elastic constants (in GPa), obtained by fitting the spectroscopic data, are C11 = 181.9 ± 0.3, C33 = 66.8 ± 0.8, C44 = 42.8 ±0.2, C12 = 48.2 ± 0.5, C13 = 27.1 ± 1.0, C14 = 5.4 ± 0.5, and C66 = (C11-C12) = 66.9 ± 0.3 GPa. The VRH averages of bulk and shear modulus are 63 and 49 GPa, respectively. The aggregate Poisson ratio is 0.19. The high value of the ratio C11/C33 = 2.7 and of the ratio C66/C44 = 1.6 are characteristic of an anisotropic structure with very weak interlayer interactions along the c-axis. The basal plane (001) is characterized by 0.1% longitudinal acoustic anisotropy and 0.9-1.1% shear acoustic anisotropy, which gives alunite a characteristic pseudo-hexagonal elastic behavior, and is related to the pseudo-hexagonal arrangement of the Al(O,OH)6 octahedra in the basal layer. The elastic Debye temperature of alunite is 654 K. The large discrepancy between the elastic and heat capacity Debye temperature is also a consequence of the layered structure. © Springer-Verlag 2006.
Keywords: ALUNITE; CRYSTAL STRUCTURE; ELASTIC CONSTANTS